'One of us': The queer afterlife of Margaret Thatcher as a gay icon. (1st September 2012) - Janes, Dominic
In recent years Margaret Thatcher has come to be represented as a gay icon by a number of prominent right-wing gay men in Britain. This appears to clash with her record in office, on the basis of which she has previously been seen as a staunch enemy of gay liberation. The origins of a queer presentation of the former Prime Minister lie in the attacks made upon her during her time in office which portrayed her as androgynous and perverse. Such attacks were based on the complicated and ambivalent position she occupied by virtue of being a radical pioneer in her career and a believer in traditional moral standards. Aspects of her ambiguous image were subsequently available for appropriation by interest groups, such as Conservative gay men, who wished to obscure the political record of her government in the context of attempts to legitimate their status within their party in the twenty-first century. There has been extensive study of the ways in which movie stars and other public figures have been established as inspirational figures for the gay community, but the example of Thatcher is exceptional in that she was previously widely attacked for presiding over an allegedly homophobic government. The study of the queer afterlife of Margaret Thatcher as a gay icon, therefore, develops understanding of the ways in which the canon of gay iconicity is a contested cultural field.